Mekanisme Penyelesaian Sengketa Informasi Publik di Pengadilan Tata Usaha Negara Denpasar - I Made Bayu Ari Budi Utama; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Preferensi Hukum, 2020)
The sustainability of public information is an inseparable aspect of democracy, which upholds freedom and human rights. The sustainability of public information is an important aspect in fulfilling individual rights to public information. However, in practice, the public's understanding of the dispute resolution mechanism on the Sustainability of Public Information is still low. In addition, in the implementation of this Public Information Sustainability dispute, there are still obstacles that can interfere with the implementation process. That can be in the form of the applicant's lack of interest in requesting information and the applicant's lack of understanding of the administrative process in dispute implementation. Based on these problems, the purpose of this study is to know the efforts to resolve public information disputes and practice the process of dispute resolution on the sustainability of public information. The research method used is the empirical method assisted by primary and secondary legal material sources and uses qualitative techniques, namely by describing legal data first, then analyze through analysis techniques with interpretive techniques and shed descriptively in the form of a thesis. Efforts to resolve public information disputes can be carried out through two processes, namely the non-litigation process carried out at the competent Regional Information Commission and the litigation process undertaken at the State Administrative Court if the disputing public body is a State-owned public agency or a PN if the disputing public body is said. is a private public body. In practice, the process of resolving information sustainability disputes in Indonesia still has obstacles which can be in the form of misunderstandings caused by the applicant's lack of understanding of the application mechanism or the stages of the administrative process that must be passed in filing a dispute on the sustainability of public information.